Lecturers’ Experiences of the Blurring of Work and Home Boundaries During the Covid-19 Pandemic at a South African ODeL University - Katharine Naidu; Mpho-Entle Puleng Modise (Open Praxis, 2023)
The unprecedented extended Covid-19 pandemic lockdowns forced higher education institutions (HEIs) to find innovative ways to effectively deliver student tuition and support. The lockdown brought many challenges to the education sector, including increasing the blurring of the work–home boundaries. This study investigated how Covid-19 accelerated the blurring of lecturers’ work–home boundaries in the College of Education at a distance education institution in South Africa. Semi-structured interviews were used to collect data from 15 lecturers. The results showed that a lack of workspace at many lecturers’ homes forced them to work beyond normal office hours. One of the key findings was that complete segmentation and integration were impossible because these lines were continuously blurred during the pandemic. The demand for immediate feedback by students exacerbated the situation for many lecturers. There is a need for the design of fluid policies that can be readily implemented during times of emergency such as the pandemic.